Case Report: Diagnosis of Petrous Apex IgG4-Related Disease by Middle Cranial Fossa Craniotomy and Temporal Bone Biopsy - Hofmeyr, Louis; Herbst, Gerrida; Pretorius, Elias; Sarembock, Brian; Taylor, Kathryn; Roytowski, David (Frontiers in Neurology, 2022)
Introduction: Primary IgG4-related disease (IgG4-RD) of the temporal bone is a rare condition. Unlike typical petrous apicitis or Gradenigo syndrome, our patient presented exclusively with a unilateral cranial nerve six palsy and symptoms of diplopia. Skull base imaging demonstrated a destructive boney lesion in the petrous apex. Imaging and systemic investigations were insufficient to support a diagnosis. The diagnosis was achieved histologically after acquiring the specimen via a middle fossa craniotomy (MFC) and temporal bone biopsy. This case report is thought to be the first published description of a diagnosis of IgG4-RD proven via the MFC approach. Case Report: We describe a 29-year-old female with primary IgG4-RD of the petrous apex of the temporal bone. This patient presented with a few months history of left-sided headache and recent-onset diplopia due to a paralysis of cranial nerve six. Imaging demonstrated a petrous apex lesion; comprehensive systemic investigations could not reach a diagnosis. A middle fossa craniotomy and biopsy of the temporal bone lesion was undertaken to establish the diagnosis. Histological confirmation of IgG4-RD was proven. Following treatment with corticosteroids, the patient experienced complete recovery and resolution of her symptoms. Conclusion: This case study describes primary IgG4-RD of the petrous apex of the temporal bone, presenting with diplopia and diagnosed with a middle cranial fossa craniotomy and temporal bone biopsy. To the best of our knowledge, this is the first case description where the primary diagnosis was made on a middle cranial fossa craniotomy and temporal bone biopsy.